Study on the technology of ultrasonic assisted combined extraction of saponins and polysaccharides from Polygonatum sibiricum and its hypoglycemic activity - XIE Bingzong; LI Mi; DONG Caiwen; WANG Xin; LIU Han; MA Yanli (Shipin yu jixie, 2024)
Objective: With the Polygonatum sibiricum as raw material, to develop a process for the combined extraction of Polygonatum sibiricum sponins (PSSs) and polysaccharides (PSPs), and the inhibitory activities of the extract and their complexes (PSSs-PSPs) on α-glucosidase and α-amylase were investigated. Methods: PSSs and PSPs were performed using ultrasound combined with enzymatic hydrolysis. The effects of solid-liquid ratio, ultrasonic time, and ultrasonic temperature on the yield of PSSs, the types of multi-enzymes, the proportion of complex enzymes, enzymolysis time, enzyme dosage, solid-liquid ratio, hot water extraction time, and hot water extraction temperature on the yield of PSPs were investigated, and the Box-Behnken experiment design was used to optimize the extraction of PSSs and PSPs. Results: The optimum extraction parameters of PSSs and PSPs were as follows: ultrasonic temperature was 50 ℃, ultrasonic time was 50 min, ultrasonic solid-liquid ratio was 1∶25 (g/mL), enzymolysis time was 2 h, enzyme dosage was 3 053 U/g, solid-liquid ratio was 1∶25 (g/mL), hot water extraction temperature was 80 ℃, and hot water extraction time was 1 h. Under the control of these conditions, the total yield of PSSs and PSPs was 12.22% and the 27.07%. The inhibitory activities of the extract and their complexes (PSSs-PSPs) on α-glucosidase and α-amylase were verified, and their complexes also have a good inhibitory effect on those enzymes. Conclusion: The process conditions for the efficient synergistic extraction of polygonatin and polysaccharide were obtained after optimization. Compared with a single component, the hypoglycemic activity of their complexes was improved.